2016
DOI: 10.1016/j.actbio.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin hydrogels functionalized with cartilage extracellular matrix and incorporating freshly isolated stromal cells as an injectable for cartilage regeneration

Abstract: An alternative to the use of in vitro expanded cells in regenerative medicine is the use of freshly isolated stromal cells, where a bioactive scaffold or hydrogel is used to provide an environment that enhances their proliferation and tissue-specific differentiation in vivo. The objective of this study was to develop an injectable fibrin hydrogel functionalized with cartilage ECM micro-particles and the growth factor TGF-β3 as a therapeutic for articular cartilage regeneration. This study demonstrates that fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 49 publications
3
89
0
Order By: Relevance
“…cECM independently enhanced chondrogenesis at day 7, but the chondroinductive effect decreased by day 21. Rather, medium supplementation with TGF-β was required for sustained upregulation of chondrogenic markers, with corresponding deposition of cartilage ECM proteins; this finding agrees with related work [27, 28, 65]. Despite the apparent necessity of exogenous TGF-β for robust cartilage formation, cECM within the hydrogel interacted synergistically with the supplemented TGF-β, as demonstrated by the greatest increases in chondrogenic gene expression and sGAG deposition seen in the cECM + TGF-β group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…cECM independently enhanced chondrogenesis at day 7, but the chondroinductive effect decreased by day 21. Rather, medium supplementation with TGF-β was required for sustained upregulation of chondrogenic markers, with corresponding deposition of cartilage ECM proteins; this finding agrees with related work [27, 28, 65]. Despite the apparent necessity of exogenous TGF-β for robust cartilage formation, cECM within the hydrogel interacted synergistically with the supplemented TGF-β, as demonstrated by the greatest increases in chondrogenic gene expression and sGAG deposition seen in the cECM + TGF-β group.…”
Section: Discussionsupporting
confidence: 89%
“…The inclusion of cartilage ECM structural proteins such as collagen type VI [62], collagen type II, and proteoglycans [63, 64] within MSC-seeded hydrogels has been found to enhance chondrogenic differentiation. Similarly, Almeida et al [28, 65] reported similar improvements when using decellularized cartilage ECM particles. In this study, cECM was mixed with photocrosslinkable GelMA hydrogels, a biomaterial which we previously found to support robust chondrogenesis [8].…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, the inclusion of a water-soluble, visible light-responsive photoinitiatior (i.e., LAP) obviates concerns of possible cellular damage caused by UV light exposure, as required by most photoinitiators (e.g., Irgacure) [24]. While the effect of meniscal ECM supplementation on MSC-seeded GelMA hydrogels was previously unexplored, functionalization of GelMA with particulated (hyaline) cartilage ECM has been reported to enhance chondrogenesis of encapsulated MSCs [29, 30]. Although the particulated ECM was presumably chondroinductive due to retention of intrinsic chondrogenic cues, robust chondrogenesis required stimulation with exogenous TGF-β3.…”
Section: Discussionmentioning
confidence: 99%
“…128,129,130,131 Benavides et al 132 have applied fibrin-based hydrogels, together with PEG and human amniotic fluid-derived stem cells, to develop a novel injectable hydrogel system that is able to induce a fibrin-driven angiogenic host response and promote in situ amniotic fluid-derived stem cell-derived neovascularization. Almeida et al 133 have developed an injectable, cartilaginous ECM microparticle-functionalized fibrin-based hydrogel, which transforms growth factor transforming growth factor-β 3 into a putative therapeutic for articular cartilage regeneration. The capacity of the hydrogel to promote chondrogenes is of freshly isolated stromal cells in vivo suggests that the hydrogel can induce cartilage formation and has the potential for cartilage repair, and thus may have the potential to overcome several current challenges related to cartilage tissue engineering.…”
Section: Injectable Hydrogels Prepared With Different Biomaterialsmentioning
confidence: 99%